THE JUDICIARY SYSTEM AND THE SOCIAL CARE SYSTEM POLICY ON CONTRACTUAL CAPACITY: OVERVIEW OF RESEARCH CONDUCTED IN THE CITY OF BELGRADE - Peric, Sandra; Sjeničić, Marta; Marčetić , Dragana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Contractual capacity is the starting point for exercising most human rights. It entails the capacity to sign contracts and enter into the legal transactions, and it is a gateway to exercising a range of labour, voting, family, property, succession (etc.) rights envisaged by the law. The full deprivation of contractual capacity leads to the deprivation of most other capacities. Thus, a person is de iure and de facto excluded from societal life. The mechanism for deprivation of contractual capacity exists in both domestic and foreign jurisprudence, as a way of protecting individual rights. The deprivation of contractual capacity in adults is applicable when the competent authority determines one’s mental or intellectual impairment. In the past, the prevailing approach to establishing such disability was the medical approach, which is largely the same today, while the social model is seldom applied. The issue of protection of the right to contractual capacity has seldom been comprehensively analyzed, either from the standpoint of social care services or from the standpoint of jurisprudence. Yet, they are both equally relevant in the process of assessing contractual capacity. This paper presents the results of research conducted in social care centers and courts in the territory of the City of Belgrade (Serbia). The research was aimed at establishing whether the status and position of social care service users has improved after introducing the legal mechanism authorizing the courts to assess (within a specific time limit) if there are reasons for continuing the imposed measure of deprivation of contractual capacity, as well as to analyze the major reasons for initiating the legal action for reassessment of contractual capacity.